An Islamic Law Design In The Realm Of The National Legal Politics - Winardi Winardi (Nagari Law Review, 2021)
The political dynamics of the national law shows that the existence of the Islamic law has ups and downs following the existing social dynamic and political configuration. It needs serious efforts to dig up and socialize as many as possible noble values contained in the Islamic law. The ways to dig up the values, among others, are to understand philosophical aspects of the Islamic law as mirrored from the kulli (sharia law) serving as the basis of its thought, the goals of the Islamic law (maqashid al-syariat) including their wisdom (hikmah al-tasyri’), and also the concept of human beings according to Islam. The Islamic law as the source of values for rules of laws that will be made, is implemented using how the values of the laws are obtained and then poured down into the national law. The majority of Muslim and Islamic prominent leaders seem to consider that the implementation of the Islamic law may be accommodated without any formal legislation as Islamic law, but by merely integrating principles of the Islamic law into the national law. Such an integration into the national law is probably made especially under the framework of the national law development.